A nitrogen-doped NiCo2S4/CoO hollow multi-layered heterostructure microsphere for efficient oxygen evolution in Zn–air batteries. Issue 2 (22nd December 2020) - He, Bin; Song, Juan-Juan; Li, Xiao-Yu; Xu, Chun-Yu; Li, Yi-Bo; Tang, Ya-Wen; Hao, Qing-Li; Liu, Hong-Ke; Su, Zhi
Abstract : Exploring highly effective and low-cost non-noble metal-based electrocatalysts for oxygen evolution reaction (OER) is critical for renewable energy conversion and metal–air batteries. Abstract : Exploring highly effective and low-cost non-noble metal-based electrocatalysts for oxygen evolution reaction (OER) is critical for renewable energy conversion and metal–air batteries. Herein, a novel and high-efficient OER catalyst was reported with nitrogen-doped oxide/sulfide heterostructures (named N-NiCo2 S4 /CoO microsphere). The N-NiCo2 S4 /CoO microsphere was synthesized by annealing NiCo-BTC MOF to a multi-layered hollow structure of NiCo2 O4 microspheres, followed by the direct vulcanization in the presence of NH4 HCO3, resulting in an oxide/sulfide heterojunction. Benefiting from the nitrogen doping, the abundant multi-layered hollow heterostructure and the interfaces between multiple components, the N-NiCo2 S4 /CoO microsphere exhibited excellent OER activity with a low overpotential of 227 mV at 10 mA cm −2 . The Zn–air battery based on the N-NiCo2 S4 /CoO + Pt/C catalyst displayed excellent cycling stability after 900 cycles at a large current density of 5 mA cm −2, where the commercial RuO2 + Pt/C-based battery exhibited a big drop after only 30 cycles, suggesting its great application prospects as power source devices.